REHABILITASI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO SINAR CATUR TUNGGAL DI DESA PAKISAN - Suryawan, A.A.A.; Suarda, M.; Suweden, I N.; Suputra, I G.N.O. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Micro Hydro Power (MHP) of ‘Sinar Catur Tunggal’ group has a generator capacity of 10 kVA which was built in 1987 in the Antaban sub-village of Pakisan village, Buleleng-Bali, by a team from University of Brawijaya. However, the MHP is not working since 2010 has not been fixed because of the limited budget and technical capabilities of the group members. Considering that this MHP is very important to supply electrical energy for the communities of Pakisan village, especially in the Antaban sub-village where is not covered by the state electrical system, therefore it is much needed assistance to rehabilitate them. Once rehabilitated, the MHP system ‘Sinar Catur Tunggal’ has been able to operate normally and relatively smooth without a noisy sound. However, due to the discharge of water supply to turbine less than the design flow of 200 liters/sec, the voltage of electricity generated is only 150 Volt. In addition, the new control panel of the power distribution can protect the generator/alternator from a short circuit. This has been demonstrated by the operator that any occurrence of surge in one of the customers/communities electrical grid then it switch (MCB) on the control panel will be off, and do not disturb the overall system. By this rehabilitation, the 40 families of Antaban sub-village in Pakisan village can take back electrical power for their everyday needs.